LITERATURE REVIEW PENGGUNAAN ARTIFICIAL INTELLIGENCE (AI) DI KALANGAN MAHASISWA DALAM DUNIA PENDIDIKAN - Nurjannah, Nurjannah; Tjahjono, Budi; Siregar, Sarah Veronica; Basyarewan, Humairoh (Politeknik Bisnis Indonesia, 2024)
Rapid digital transformation has changed the paradigm of higher education, with Artificial Intelligence (AI) becoming one of the key technologies that supports adaptive and personalized learning. However, its implementation faces significant challenges, such as issues of ethics, data privacy, and academic integrity. This research aims to evaluate the effectiveness and challenges of using AI in higher education, especially by students, as well as formulating strategic recommendations for integrating this technology responsibly. Using a literature review approach, this research analyzes trends, benefits, and barriers related to AI applications such as AI-Based Intelligent Assistants (AIIA). The research results show that AI can improve learning efficiency and provide a more personalized learning experience, but concerns about technology dependency, potential plagiarism, and ethical and social impacts remain major obstacles. This research concludes that although AI has great potential in higher education, its successful integration requires strategic policies that consider technical, pedagogical and ethical aspects. This study contributes to the development of AI technology management strategies in higher education, providing guidance for creating an inclusive, adaptive, and sustainable learning ecosystem.